2019
DOI: 10.1002/ijgo.12891
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic accuracy of International Ovarian Tumor Analysis simple rules and the risk of malignancy index to discriminate between benign and malignant adnexal masses

Abstract: Objective:To compare the diagnostic accuracy of International Ovarian Tumor Analysis (IOTA) simple rules and risk of malignancy index (RMI 1/RMI 2) scoring to discriminate between benign and malignant adnexal masses.Methods: Secondary analysis of a cohort of patients scheduled for surgery for adnexal masses in a tertiary center between April 2010 and March 2018. Ultrasound examinations were performed by general gynecologists within 24 hours prior to surgery to evaluate sonographic features. Demographic data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 13 publications
2
36
3
Order By: Relevance
“…It has been suggested that neoplasms are irregular solid tumor; multilocular and irregular masses of 10cm or more; presence of septa with a thickness of 2-3 mm; presence of at least 3 papillary projections; increased vascularization; evidence of ascites; or peritoneal masses. Even though there are no data showing the efficacy of this model in pregnancy, it is probable that its validity is applicable also in evaluating masses during pregnancy [ 8 , 9 ]. In case of non-conclusive ultrasound, or when a wider assessment of tissue planes and relation to other organs may be important in both obstetric and surgical planning, magnetic resonance imaging (MRI) can be a useful.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that neoplasms are irregular solid tumor; multilocular and irregular masses of 10cm or more; presence of septa with a thickness of 2-3 mm; presence of at least 3 papillary projections; increased vascularization; evidence of ascites; or peritoneal masses. Even though there are no data showing the efficacy of this model in pregnancy, it is probable that its validity is applicable also in evaluating masses during pregnancy [ 8 , 9 ]. In case of non-conclusive ultrasound, or when a wider assessment of tissue planes and relation to other organs may be important in both obstetric and surgical planning, magnetic resonance imaging (MRI) can be a useful.…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of the IOTA Simple Rules is the possibility of inconclusive results when they do not apply. According to previous reports, the proportion of inconclusive results could be as high as 20% [ 9 , 10 ]. A “two-step strategy” using the IOTA Simple Rules with the addition of subjective assessment for masses with inconclusive results was proposed and proved to have excellent test performance comparable to that of subjective assessment alone [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For pre-surgical diagnosis of women with adnexal masses, the American College of Obstetrics and Gynecology recommends a multivariable approach by combining demographic, clinical, laboratory, and imaging parameters to achieve better diagnostic accuracy [ 3 , 14 ]. Even though the application of IOTA Simple Rules has recently been proven acceptably accurate in our setting [ 9 ], we hypothesized that its accuracy could be further improved by including other relevant parameters such as serum CA-125. The primary aim of this study was to evaluate the diagnostic added-value of serum CA-125 to the IOTA Simple Rules, without subjective assessment, to differentiate between malignant and benign ovarian tumors before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are no data showing the efficacy of this model in pregnancy, it is probable that its validity is applicable also in evaluating masses during pregnancy. 7,12 Ultrasound has some limitations. The augmented uterine volume after the 20th week of pregnancy makes it difficult to assess adnexal masses precisely.…”
Section: Introductionmentioning
confidence: 99%